Observational Test of the Global Moving Hot Spot Reference Frame - Chengzu Wang; Richard G. Gordon; Tuo Zhang; Lin Zheng (Geophysical Research Letters)
Abstract The Global Moving Hotspot Reference Frame (GMHRF) has been claimed to fit hot spot tracks better than the fixed hot spot approximation mainly because the GMHRF predicts ≈1,000 km southward motion through the mantle of the Hawaiian mantle plume over the past 80 Ma. As the GMHRF is determined by starting at present and calculating backward in time, it should be most accurate and reliable for the recent geologic past. Here we compare the fit of the GMHRF and of fixed hot spots to the observed trends of young tracks of hot spots. Surprisingly, we find that the GMHRF fits the data significantly worse (p = 0.005) than does the fixed hot spot approximation. Thus, either plume conduits are not passively advected with the mantle flow calculated for the GMHRF or Earth's actual mantle velocity field differs substantially from that calculated for the GMHRF.